144k views
5 votes
Multiply using the FOIL method:
(x + y) (x + 2)

2 Answers

6 votes

Answer:

Explanation:

F - First ; O - Outside ; I - inside ; L -last

(x + y)(x + 2) = x*x + x*2 +y*x +y*2

= x² + 2x + xy +2y

Multiply using the FOIL method: (x + y) (x + 2)-example-1
User Samuli Asmala
by
5.1k points
2 votes

Answer:

x^2 +2x+xy +2y

Explanation:

(x + y) (x + 2)

FOIL

first x*x = x^2

outer x*2 =2x

inner y*x= xy

last = y*2 =2y

Add together

x^2 +2x+xy +2y

User Florin Secal
by
4.4k points